Legal Norms and Principles of Decentralization of Authorities in Handling the Covid-19 Pandemic - Wahyuni, Irma Indra; Huda, Mokhamad Khoirul (Lex Publica, 2021)
Covid-19 is a virus originating from Wuhan, China, which has spread throughout almost the world. In Indonesia, the virus spread began on March 2, 2020, allegedly starting from an Indonesian citizen who had direct contact with a foreign citizen from Japan. Over time, the spread of Covid-19 has experienced a significant increase. Due to the delay in anticipating and handling Covid-19 by the government, the government did not immediately determine the status of handling Covid-19, so the flow of coordination between the central government and regional governments became unclear in handling the substance, and technical aspects of Covid-19 in the Central Government and Regional governments experience overlapping authorities because there are arrangements in several laws that contradict each other and are not in harmony between the Central Government, Regional Governments and Duties and National Disaster Management Agency (Badan Nasional Penanggulangan Bencana/BNPB) so as to allow for the handling of the Covid-19 disaster. Thus, it is important to study whether the government’s authority central and regional governments under the control of Covid-19 have been and are in accordance with the structure, duties, functions, as well as applicable regulations and the extent to which the consequences are due to the overlapping of central and regional authorities in the grip of the Covid-19 pandemic and how to deal with it. The legal responsibility of the Central and Regional Governments due to the slow handling of Covid-19. Abstrak Covid-19 merupakan virus yang berasal dari Wuhan, China yang menyebar di hampir seluruh dunia Di Indonesia Penyebaran virus ini dimulai sejak tanggal 02 Maret 2020, diduga berawal dari salah satu warga negara Indonesia yang melakukan kontak langsung dengan warga negara asing yang berasal dari Jepang. Seiring dengan berjalannya waktu, penyebaran Covid-19 telah mengalami peningkatan yang signifikan. Meningkatnya kasus Covid-19 salah satunya disebabkan Karena adanya Keterlambatan antisipasi dan penanganan Covid-19 oleh pemerintah, pemerintah tidak segera menentukan status penanganan Covid-19 sehingga alur koordinasi antara pemerintah pusat dan pemerintah daerah menjadi tidak jelas Dalam penanganan substansi dan teknis Covid-19 di lapangan Pemerintah Pusat dan pemerintah daerah mengalami tumpang tindih kewenangan karena ada pengaturan di dalam beberapa Undang- Undang yang saling bertolak belakang dan tidak harmoni antara Pemerintah Pusat, Pemerintah daerah dan gugus Tugas serta Badan Nasional Penanggulangan Bencana (BNPB) sehingga berpotensi memperpanjang birokrasi penanggulangan bencana Covid-19. Dengan demikian, penting untuk dikaji adalah Apakah kewenangan pemerintah pusat dan daerah dalam menangani Covid-19 telah efektif dan sesuai dengan struktur, tugas, fungsi, serta peraturan-peraturan yang berlaku serta Sejauh mana akibat yang ditimbulkan karena adanya Tumpah Tindih kewenangan Pusat dan daerah dalam menangani Pandemi Covid-19 dan bagaimana pertanggung jawaban hukum Pemerintah Pusat dan Daerah akibat lambatnya Penanganan Covid-19. Kata kunci: Covid-19, Kewenangan ,Pemerintah Pusat, Pemerintah Daerah, Pertanggungjawaban Hukum